Can Inheritances Alleviate the Demographic Burden? - Lueth, Erik (IMF Working Papers; Working Paper, 2001)
With pay-as-you-go schemes in place, population aging will impose a heavy fiscal burden on young and future cohorts. However, these cohorts may also profit from larger inheritances as the number of heirs declines. The aim of this paper is to explore the compensating potential of private intergenerational transfers. A dynamic, computable general equilibrium model is employed allowing for a pay-as-you-go scheme, various bequest motives, and an endogenous labor supply. The findings are twofold. First, the increase in future generations' inheritances is insufficient to make up for the demographic burden. Second, increasing the inheritance tax during the demographic transition may alleviate the fiscal burden of future generations by improving overall efficiency.